Improvement of low-oil gelatin emulsions performance by adjusting the electrostatic interaction between gelatin and nanocellulose with different morphologies. (May 2023) - Feng, Xin; Dai, Hongjie; Tan, Hongxia; Tang, Mi; Ma, Liang; Zhang, Yuhao
Abstract: This work investigated the effect of different pH values (4, 7, 11) and nanocellulose morphologies (cellulose nanocrystals (CNCs), cellulose nanospheres (CNSs), and cellulose nanofibrils (CNFs)) on the low-oil gelatin emulsions performance. Results showed the electrostatic complex (pH = 4) transformed into complexes in the form of free molecules (pH = 11), reduced the interaction between gelatin and nanocellulose. The emulsion showed smaller creaming index (CI, 0–49.55%) and larger D4, 3 (30.47–44.63 μm) at pH = 7 in comparsion with pH = 4 (0–59.17%, 28.1–35.1 μm) and pH = 11 (0–58.54%, 21.3–29.47 μm). The microstructure showed the composition of interfacial film was changed from electrostatic complexes (pH = 4) to gelatin (pH = 7) due to competitive adsorption, and the nanocellulose was filled into the continuous phase to form a compact network. While the strong electrostatic repulsion (pH = 11) weakened the network strength, indicating the emulsion at pH = 7 has relatively high stability. Moreover, the nanocellulose morphologies also acted a crucial role in adjusting the properties and network structure of emulsions. The interfacial results displayed the interfacial adsorption of G-CNCs was restrained (84.12%) significantly ( p  < 0.05) at pH = 7, which reduced the interface stability, but formed a compact cellulose network, G-CNSs and G-CNFs could form relatively loose network due to small size or easy aggregation. It suggested the G-CNCs at pH = 7 was more conducive to the establishment of stable emulsions. Hence, this work would offer a guiding significance for the practical production of low-oil gelatin emulsions. Graphical abstract: Image 1 Highlights: Low-oil gelatin emulsions were fabricated at different pH and nanocellulose morphologies. Nanocellulose improved the low-oil gelatin emulsions performance obviously. The tightest network in the continuous phase was formed at pH = 7. The emulsion stabilized by G-CNCs showed high stability at pH = 7. The emulsion droplets generated at pH = 11 weakened cellulose network.